A concomitant loss of dormant origins and FANCC exacerbates genome instability by impairing DNA replication fork progression. Issue 9 (3rd March 2014) - Luebben, Spencer W.; Kawabata, Tsuyoshi; Johnson, Charles S.; O'Sullivan, M. Gerard; Shima, Naoko
Abstract: Accumulating evidence suggests that dormant DNA replication origins play an important role in the recovery of stalled forks. However, their functional interactions with other fork recovery mechanisms have not been tested. We previously reported intrinsic activation of the Fanconi anemia (FA) pathway in a tumor-prone mouse model ( Mcm4 chaos3 ) with a 60% loss of dormant origins. To understand this further, we introduced a null allele of Fancc ( Fancc − ), encoding a member of the FA core complex, into the Mcm4 chaos3 background. Primary embryonic fibroblasts double homozygous for Mcm4 chaos3 and Fancc − ( Mcm4 chaos3/chaos3 ;Fancc −/− ) showed significantly increased levels of markers of stalled/collapsed forks compared to either single homozygote. Interestingly, a loss of dormant origins also increased the number of sites in which replication was delayed until prophase, regardless of FA pathway activation. These replication defects coincided with substantially elevated levels of genome instability in Mcm4 chaos3/chaos3 ;Fancc −/− cells, resulting in a high rate of perinatal lethality of Mcm4 chaos3/chaos3 ;Fancc −/− mice and the accelerated tumorigenesis of surviving mice. Together, these findings uncover a specialized role of dormant origins in replication completion while also identifying important functional overlaps between dormant origins and the FA pathway in maintaining fork progression, genome stability, normal development and tumor suppression.